Growth Through 24 Months of Age in Infants Receiving Formulas with or Without Added Bovine Milk Fat Globule Membrane (MFGM) or Human Milk Through the First Year of Life: An RCT. (29th May 2020) - Ospina, Angela Jaramillo; Toro, Rosario; Murguia-Peniche, Teresa; Wampler, Jennifer; Wu, Steven; Berseth, Carol Lynn; Uauy, Ricardo
Abstract: Objectives: To evaluate growth through 24 months of age in infants receiving added bovine milk fat globule membrane (MFGM) in infant formula through 12 months of age. Concentration of MFGM from bovine milk fractions and incorporation in infant formula may better approximate the composition of complex milk lipids in human milk. Methods: In the double-blind, randomized, controlled Chilean Infant Nutrition Trial (ChiNuT; NCT0262613), term infants whose mothers chose to initiate exclusive infant formula feeding before 4 months of age were randomized to receive: a standard cow's milk-based infant formula (SF, n = 174) or a similar formula with added whey protein-lipid concentrate (5 g/L; source of bovine MFGM) (bMFGM, n = 176). A reference group of infants exclusively receiving human milk (HM, n = 236) was also recruited. Growth through 24 months of age was the primary outcome. Length-for-age (LAZ), weight-for-age (WAZ) and body mass index (BMI)-for-age (BAZ) growth z-scores were analyzed by mixed-effects multiple linear regression models adjusted by sex, age (days), and maternal pregestational BMI (kg/m2). Results: No significant group differences in sex, gestational age at birth, birthweight, maternal age and maternal education were detected, with the exception of maternal pregestational BMI (mean(SD)) (HM: 27.0(5.2) lower vs SF: 28.6(6.2) or bMFGM: 28.9(6.1); P = 0.002). Groups were similar at baseline (weight, length, WAZ, BAZ) with the exception of LAZ (lower in the bMFGM compared to HM group; P < 0.05). No significant differences in growth z-scores (absolute at 6, 9, 12, and 24 months of age or change between baseline and each study time point) were detected between SF and MFGM groups. Both randomized study formula groups were associated with higher growth z-score increases from baseline compared to the HM reference group between 6 and 24 months (P less than 0.05). Mean growth z-scores fell within the range of −1 to 1 (16th to 84th percentile) for SF, bMFGM, and HM groups at all study time points. Conclusions: Added bovine MFGM in a routine cow's milk-based infant formula through 12 months of age supported normal growth through 24 months of age. Funding Sources: The study was funded by Mead Johnson Nutrition (MJN). Teresa Murguia-Peniche, Steven Wu, and Jennifer Wampler are currently employed by MJN. Carol Lynn Berseth was previously employed by MJN.